2019
DOI: 10.1111/phpp.12465
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tanning behavior assessed via online survey: Attitudes, habits, and preventive measures with focus on sunscreen use

Abstract: Background/purpose: Incidence of melanoma is increasing globally. Exposure to ultraviolet radiation (UVR) as important risk factor for developing skin cancer can be influenced by tanning behavior. Only a few studies are available concerning sun tanning behavior and protective measures.Methods: An online survey was distributed via social media to assess tanning habits and examine associated demographic and behavioral factors. Results:In total, 403 questionnaires were distributed, and mean age of respondents was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The Asian beauty ideal of fair skin can be contrasted with the European ideal of tanned skin to signify beauty and health, such as demonstrated in the German population. 34 The search interest in German-speaking countries reflect this trend, with more queries for tanning beds compared with sunscreen. 24 South-East Asia does not experience four seasons, and hence, regional search patterns would be less likely to exhibit seasonality.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Asian beauty ideal of fair skin can be contrasted with the European ideal of tanned skin to signify beauty and health, such as demonstrated in the German population. 34 The search interest in German-speaking countries reflect this trend, with more queries for tanning beds compared with sunscreen. 24 South-East Asia does not experience four seasons, and hence, regional search patterns would be less likely to exhibit seasonality.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the abundance of natural sunlight in the tropical climate further reduces the likelihood of the use of solaria and tanning beds given the prevailing cultural norms that value those with fairer complexions. The Asian beauty ideal of fair skin can be contrasted with the European ideal of tanned skin to signify beauty and health, such as demonstrated in the German population . The search interest in German‐speaking countries reflect this trend, with more queries for tanning beds compared with sunscreen .…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the common misconception that applying sunscreen reduces the likelihood of achieving a tan. This is a lower percentage than in a study conducted in Germany, which found that 98% of its participants use sunscreen as a protective precaution while on vacation and slightly fewer while tanning 93% [ 17 ].…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, focusing on popular topics can be a way to convey important messages about other important dermatological issues. Schneiderbanger et al [ 35 ] presented an interesting example of how dermatologists’ concerns about a disease (skin cancer) can be associated with the main interests of young females (skin aging). Since the prevention of skin aging seems to be an important concern among young females, a dermatologist could broadcast a video emphasizing the association between tanning and premature skin aging, thus helping discourage this behavior and, therefore, contributing to reducing the prevalence of skin cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%